Septic tank base plate and septic tank
By using a fiber-reinforced concrete foundation plate for septic tanks that replaces cement with binders like blast furnace slag powder and slaked lime, the durability and environmental impact of septic tank installations are enhanced.
Patent Information
- Application Number
- JP2025000700U
- Authority / Receiving Office
- JP · JP
- Patent Type
- Utility models
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2035-03-05
AI Technical Summary
Existing septic tank foundation plates made from fiber-reinforced concrete with cement as a binder are not durable enough and contribute to high CO2 emissions during manufacturing.
A septic tank foundation plate made from fiber-reinforced concrete that does not use cement as a binder, instead employing fine blast furnace slag powder, silica fume, expanding material, and slaked lime as binders, along with glass fibers and water, to enhance durability and reduce emissions.
The solution reduces CO2 emissions during manufacturing and improves the durability of the septic tank foundation plate, making it more resistant to deterioration and suitable for outdoor use.
Smart Images

Figure 0003251167000001_ABST
Abstract
Description
[Technical field]
[0001] This invention relates to a foundation plate for a septic tank, which is used when constructing a septic tank by burying it underground, and to the septic tank itself. [Background technology]
[0002] As can be seen from Figure 1, a septic tank is usually installed by digging a hole in the ground at the installation site to the size of the septic tank 1, pouring broken chestnuts 3 into the bottom of the hole and compacting it into a flat layer, laying a septic tank base plate 2 on top of this layer of broken chestnuts, placing the septic tank 1 on top of that, and backfilling the area around it with soil.
[0003] It is known that the above-mentioned septic tank base plate 2 is manufactured from fiber-reinforced concrete (see Patent Document 1). However, because the above-mentioned fiber-reinforced concrete uses cement as a binder, there is the problem that approximately 750 kilograms of CO2 is generated per ton of cement. In addition, fiber-reinforced concrete that uses cement as a binder and glass fiber as the fibers has the problem that it is not durable enough when used as a base plate for a septic tank.
[0004] Meanwhile, technologies have been developed that do not use cement as a binder for concrete, with the aim of reducing CO2 emissions during product manufacturing (see Patent Documents 2 to 4).
[0005] Patent Document 2 describes a concrete that does not contain cement, but contains an expansive agent, slaked lime, water, ground granulated blast furnace slag, silica fume, fine aggregate, a chemical admixture for concrete, and glass fiber, and the ratio of the mass of the slaked lime to the mass of the ground granulated blast furnace slag calculated by the following formula (1) is 0.5 to 3 mass%. (slaked lime / ground granulated blast furnace slag) x 100···(1)" (Claim 1).
[0006] Patent Document 3 describes, "A concrete binder comprising blast furnace slag and biomass combustion ash, wherein the blast furnace slag content is 50% by mass to 90% by mass, and the biomass combustion ash content is 10% by mass to 50% by mass." (Claim 1) and also states, "The present invention aims to provide a concrete binder and concrete using the same, which does not use any cement at all and therefore can completely reduce cement-derived CO2 emissions, while maintaining strength and increasing shrinkage crack resistance." (Paragraph
[0020] )
[0007] Patent Document 4 describes a concrete containing a hydraulic composition containing water and a binder, and fibers, the binder not containing cement but consisting of blast furnace slag, slaked lime, and an expanding agent, the fibers containing refractory organic fibers and spalling prevention fibers, the refractory organic fibers being 1 mm thick, and 3 "The concrete is characterized in that 3.0 kg or more of the sintered material is added per unit area of the concrete." (Claim 1) [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Utility Model Registration No. 3197423 [Patent Document 2] JP 2023-177020 A [Patent Document 3] JP 2023-38451 A [Patent Document 4] JP 2023-77790 A Summary of the Invention [Problem to be solved by the invention]
[0009] The above Patent Documents 2 to 4 do not disclose use of fiber-reinforced concrete as a base plate for a septic tank. The present invention has been made in consideration of the above-mentioned problems, and aims to provide a foundation plate for a septic tank that is highly durable without using cement as a binder, and a septic tank that uses this foundation plate. [Means for solving the problem]
[0010] In order to solve the above problems, the present invention adopts the following measures. (1) A septic tank base plate on which the septic tank is placed is made of fiber-reinforced concrete, characterized in that the fiber-reinforced concrete does not contain cement but contains ground granulated blast furnace slag, silica fume, an expansive agent, and hydrated lime as binders, and also contains fine aggregate, glass fiber, and water. (2) A septic tank placed on the septic tank base plate described above in (1). Effect of the Invention
[0011] The septic tank base plate of the present invention is made of fiber-reinforced concrete that uses a binder that does not contain cement, which reduces CO2 emissions during product manufacturing. In addition, since the binder contains little alkali, deterioration of the glass fibers is prevented, improving durability. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a schematic diagram showing the installation state of a septic tank and a septic tank base plate placed in a drilled hole in one embodiment of the present invention; [Diagram 2] FIG. 2 is a graph showing the change in bending failure load in a 70° C. hot water immersion test of the fiber-reinforced concrete of the embodiment and the fiber-reinforced concrete of the comparative example. [Diagram 3] FIG. 2 is a graph showing the change in bending fracture deflection in a 70° C. hot water immersion test of the fiber-reinforced concrete of the embodiment and the fiber-reinforced concrete of the comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An embodiment of the present invention will be described with reference to the drawings. Figure 1 shows the installation of a septic tank 1 and a septic tank base plate 2 placed in an excavated hole 4. As can be seen from this figure, the septic tank 1 is placed on top of the septic tank base plate 2, which is placed on top of a layer of broken chestnuts 3 that has been spread and compacted at the bottom of a leveled hole. Although not shown in the figure, the hole is backfilled with soil after the septic tank is installed.
[0014] The thickness of the split chestnut layer is adjusted taking into account the thickness of the septic tank base plate so that the top surface of the septic tank is roughly at the same level as the ground surface, but it is usually 80 to 100 mm or more thick. The septic tank base plate 2 has a shape that is slightly larger than the width and length of the bottom of the septic tank 1. The shape of the base plate is generally rectangular, but it may be a shape other than rectangular depending on the shape of the septic tank.
[0015] The septic tank base plate 2 of the present invention is made of a molded body of fiber-reinforced concrete. The fiber reinforced concrete does not contain cement, but contains ground granulated blast furnace slag, silica fume, an expansive agent, and hydrated lime as binders, and further contains fine aggregate, glass fiber, and water.
[0016] <Grained blast furnace slag> Ground granulated blast furnace slag is a by-product of the pig iron manufacturing process, and is made by pulverizing granulated slag that has been vitrified. Its chemical composition is CaO 33-43%, SiO2 23-33%, Al2O3 8-14%, MgO 4-10%, and its density is 2.80-3.10g / cm3. 3 and the basicity is about 1.65 to 1.95.
[0017] As the ground granulated blast furnace slag, for example, that specified in JIS A 6206 can be used. The JIS standard specifies that the Blaine specific surface area must be 4000 cm 2 / g, 6000cm 2 / g, 8000cm2 / g, and usually has a Blaine specific surface area of 4000 to 8000 cm 2 Also, some ground granulated blast furnace slag contains added gypsum, and the range of SO3 specified by JIS A 6206 is 4.0% or less, so it can be used within that range.
[0018] Ground granulated blast furnace slag hardens due to its "latent hydraulic properties," which means that it hardens by generating calcium silicate hydrate and calcium aluminate hydrate in the presence of an alkaline activator.
[0019] <Silica fume> Silica fume is collected as dust in the exhaust gas from electric arc furnaces, and most of it is amorphous and spherical silica (SiO2). This silica fume has a density of 2.30 g / cm3 as specified in JIS A 6207. 3 It is used to improve the strength of densified concrete.
[0020] <Expansion material> Expansive agents are powdered substances that expand when moisture is supplied, reducing cracks caused by drying shrinkage. For example, those that meet the quality standards set out in the Japanese Industrial Standards JIS A 6202 and other standards are used, and specific examples include calcium sulfoaluminate-based expansive agents, ettringite-lime composite expansive agents, and lime-based expansive agents. It is preferable to include an expansive material in concrete from the viewpoint of improving crack resistance and bending strength, and in this invention, an expansive material can be used as a stimulant.
[0021] <Slaked lime> Slaked lime acts as an alkaline stimulant to activate the reaction of ground granulated blast furnace slag and improve the strength and durability of concrete. For example, calcium hydroxide (Ca(OH)2) that corresponds to JIS R 9001 Special No. can be used as slaked lime. By using slaked lime, ground granulated blast furnace slag can be hardened without using any Portland cement.
[0022] <Fine aggregate> As the fine aggregate, a general fine aggregate for concrete can be used. For example, gravel and sand that meet JIS A 5308 Appendix A and have a bone dry density of 2.5 g / cm 3 Examples of fine aggregates that can be used include concrete frame sand, slag aggregates such as fine aggregates made from granulated blast furnace slag, and electric furnace oxidized slag aggregates.
[0023] <Glass fiber> The concrete of this invention is equivalent to glass fiber reinforced cement (GRC) in which the cement has been completely replaced with ground granulated blast furnace slag, and contains glass fiber. The inclusion of glass fiber increases the flexural strength and allows the concrete to be made thinner, making it possible to reduce the weight of the component.
[0024] Glass fiber is a reinforcing material used to reinforce concrete's weak point, bending strength (tensile strength). Since glass fiber deteriorates in a high-alkaline environment, it is desirable to use alkali-resistant glass fiber containing 16% or more by mass of zirconia. This invention, which does not use cement and has a low amount of added slaked lime, is characterized as a concrete that is resistant to deterioration of glass fiber.
[0025] <Chemical admixture for concrete> In concrete in which cement is replaced with ground granulated blast furnace slag, it is preferable to use chemical admixtures for concrete such as high-performance air-entraining water-reducing agents, high-performance water-reducing agents, and air-entraining water-reducing agents in order to ensure the required workability. Examples of these chemical admixtures for concrete include polycarboxylic acid ether compounds, polycarboxylic acid compounds and polyol complexes, lignin sulfonic acid compounds and polyol complexes, and naphthalene-based water-reducing agents, which correspond to JIS A 6204. These chemical admixtures for concrete may be used alone or in combination.
[0026] In the concrete of the present invention, the ratio of the mass of slaked lime to the mass of ground granulated blast furnace slag calculated by the following formula (1) is preferably 0.5 to 3.0 mass %. (Slaked lime / granulated blast furnace slag) x 100 (1)
[0027] By setting the ratio of the mass of slaked lime to the mass of ground granulated blast furnace slag to 0.5-3.0% by mass, concrete with high acid resistance, strength, and durability can be obtained without including cement. If the ratio is less than 0.5% by mass, the initial strength of the concrete may be insufficient. If the ratio exceeds 3.0% by mass, the alkalinity may increase, causing deterioration of the glass fiber and causing an insufficient acid resistance. Although the mixture ratio of slaked lime may change depending on the season, if the ratio is 1.0-2.0% by mass, concrete with high acid resistance, strength, and durability can be obtained throughout the year.
[0028] In the concrete of the present invention, the ratio of the mass of water to the mass of the binder calculated by the following formula (2) is preferably 33.0 to 42.0 mass%, where the mass of the binder is the total mass of the ground granulated blast furnace slag, silica fume, expansive agent, and hydrated lime. (Water / Binding material)×100...(2)
[0029] By making the ratio of the mass of water to the mass of the binder 33.0-42.0% by mass, concrete with high acid resistance, strength and durability can be obtained without including cement. If the ratio is less than 33.0% by mass, the amount of chemical admixture for concrete used may increase in order to prevent air bubbles and unfilled parts of the molded product caused by reduced fluidity and to prevent reduced fluidity, which may lead to an increase in material costs. If the ratio exceeds 42.0% by mass, the initial strength may decrease, voids may easily occur in the concrete after hardening, and drying shrinkage may become large, making it more likely to crack. The water mix may vary depending on the season, but if the above ratio is 35.0 to 41.0 mass %, concrete with high acid resistance, strength, and durability can be obtained throughout the year.
[0030] In the concrete of the present invention, the ratio of the mass of the binder to the mass of the aggregate calculated by the following formula (3) is preferably 55.0 to 75.0 mass%, where the mass of the binder is the total mass of the ground granulated blast furnace slag, silica fume, expansive agent, and hydrated lime. (Binder / Aggregate) × 100 (3)
[0031] By setting the ratio of the mass of the binder to the mass of the aggregate to 55.0 to 75.0% by mass, it is possible to obtain concrete that is highly acid-resistant, strong, and durable even without including cement. If the above ratio is less than 55.0% by mass, air bubbles or unfilled parts of the molded product may occur due to reduced fluidity, and the amount of glass fiber added may decrease due to the reduced fluidity, resulting in concrete with low bending strength. Also, if the above ratio is 71.0 to 75.0% by mass, concrete with high acid resistance, strength, and durability throughout the year can be obtained.
[0032] The concrete of the present invention preferably has a blast furnace slag powder content of 25.0 to 32.0 mass%, a silica fume content of 2.0 to 3.0 mass%, an expansive agent content of 1.2 to 1.6 mass%, a slaked lime content of 0.3 to 0.5 mass%, a fine aggregate content of 47.0 to 55.0 mass%, a glass fiber content of 3.0 to 3.5 mass%, a chemical admixture for concrete content of 0.4 to 0.5 mass%, and a water content of 12.0 to 13.0 mass%.
[0033] By keeping the content of each material within the above range, it is possible to obtain concrete with high acid resistance, strength, and durability even without including cement. If the content of each material is outside the above range, the balance of the concrete mix will be lost, and there is a risk of insufficient acid resistance, strength, and durability.
[0034] [Concrete manufacturing method] The method for producing concrete of the present invention includes a mixing step of mixing ground granulated blast furnace slag, silica fume, expansive agent, hydrated lime, fine aggregate, glass fiber, chemical admixture for concrete, and water, and a hardening step of hardening the mixture obtained in the mixing step.
[0035] The method for producing the glass fiber reinforced concrete in the present invention includes a general method, such as a premix method.
[0036] The premix method involves mixing ground granulated blast furnace slag, silica fume, expansive agent, hydrated lime, fine aggregate, glass fiber, chemical admixture for concrete, and water in a mixer (mixing process), and then pouring the mixture into a formwork, or molding the mixture by extrusion or pressing, and then curing it to harden (hardening process).
[0037] The fiber-reinforced concrete of the present invention is not limited to the above-mentioned method, and may be produced by, for example, mixing the respective raw materials using a direct spray method.
[0038] In the direct spray method, materials other than glass fiber are made into a slurry, the slurry is pumped and sprayed onto the formwork surface with a spray gun. At the same time, glass fiber rovings are cut to a specified length with a cutter built into the spray gun and sprayed onto the formwork surface at the same time as the sprayed slurry.
[0039] Furthermore, as shown in the "Preparation of Fiber-Reinforced Concrete Specimens" in the following Examples, the fiber-reinforced concrete of the present invention can also be manufactured by mixing the various raw materials in a manner that involves mixing materials other than glass fiber to make mortar, spreading this mortar evenly on a curing sheet, mixing chopped glass fiber into the mortar, placing roving-shaped glass fiber on top of that, spreading mortar evenly on top of that, mixing the chopped glass fiber into the mortar, and then curing the mortar. EXAMPLES
[0040] Examples and comparative examples of the present invention are given below. Fiber-reinforced concrete of Example 1 (test product) and Comparative Example 1 (conventional product) were prepared and subjected to a warm water immersion test.
[0041] Example 1 [Materials for fiber reinforced concrete] As materials for fiber-reinforced concrete, the following was prepared: 26-31 mass% granulated blast furnace slag (powder with a fineness of 4000 conforming to JIS A 6206), 2.3-2.7 mass% silica fume (silica fume conforming to JIS A 6207), 1.4-1.5 mass% expansive agent (Pacific N-EX manufactured by Pacific Materials Co., Ltd.), 0.4-0.5 mass% hydrated lime (hydrated lime conforming to JIS R 9001 Special), 49-53 mass% fine aggregate (gravel and sand conforming to JIS A 5308 Appendix A), 3.3-3.4 mass% glass roving AR5000H-530X / S (glass fiber manufactured by Nippon Electric Glass Co., Ltd.), 0.4-0.5 mass% chemical admixture for concrete, and 12-13 mass% water (tap water).
[0042] [Preparation of fiber-reinforced concrete specimens] A test specimen of the fiber reinforced concrete of Example 1 was prepared according to the following procedures (1) to (8). (1) Each material except for the glass fiber was weighed out according to the above composition and thoroughly mixed in a forced mixing mixer to produce mortar. (2) The mortar was spread evenly on the curing sheet to a thickness of approximately 3 mm. (3) Glass fibers cut from roving to lengths of approximately 10 mm to 30 mm were shaken onto the spread mortar, and the glass fibers were lightly tapped from above to mix them into the mortar. (4) On top of the glass fiber mortar approximately 3 mm thick produced by steps (1) to (3), glass fibers were placed in the form of rovings at intervals of approximately 20 mm. (5) The mortar prepared in (1) was spread evenly on top of the roving to a thickness of approximately 7 mm. (6) As in (3), the roving was cut into pieces of glass fiber approximately 10 to 30 mm long and shaken off, and the glass fibers were then lightly tapped from above to mix them into the mortar. The mass ratio of the amount of glass fiber used in (3), the amount of roving-like glass fiber used in (4), and the amount of glass fiber used in (6) was 16:11:23. (7) The test specimens, each having a thickness of approximately 10 mm, manufactured according to steps (1) to (6) were wrapped in a curing film so as to completely cover the specimens, and then cured in air for 14 days. (8) After the concrete hardened during air curing, it was cut into flat plates measuring 300 mm (length) x 250 mm (width) x 10 mm (thickness) to prepare test specimens. Multiple test specimens were prepared for each example. The test specimens were cut so that the longitudinal direction of the glass roving installed inside was parallel to the 300 mm direction (length direction).
[0043] Comparative Example 1 [Materials for fiber reinforced concrete] The materials prepared for the fiber-reinforced concrete were 10 mass% cement (corresponding to ordinary Portland cement as specified in JIS R 5210 Portland cement), 21 mass% ground granulated blast furnace slag (same as in Example 1), 3.7 mass% silica fume (same as in Example 1), 49 mass% fine aggregate (same as in Example 1), 3.3 mass% glass fiber (same as in Example 1), 0.5 mass% chemical admixture for concrete, and 12.5 mass% water (tap water).
[0044] [Preparation of fiber-reinforced concrete specimens] Each material except for the glass fiber was weighed out so as to obtain the above-mentioned composition, and thoroughly mixed in a forced mixing mixer to produce mortar.
[0045] [Hot water immersion test] The test specimens of Example 1 and Comparative Example 1 were completely immersed in 70°C hot water, and the bending breaking load and bending breaking deflection of the test specimens 1, 3, 5, 10, and 20 days after immersion were measured by performing a bending test using JIS A 1408 No. 4 test specimens. Three specimens were tested for each example, and the average of the measurements of the three specimens was calculated. In addition, the average of the bending breaking load and bending breaking deflection of the test specimens before the start of the immersion test was also calculated. The test results are shown in Figures 2 and 3.
[0046] [Test Results] The deterioration of glass fiber concrete caused by immersion in 70°C hot water for one day is said to be equivalent to the deterioration of concrete after one year of normal exposure. In other words, the 70°C hot water immersion test is an accelerated test for the deterioration of glass fiber reinforced concrete. As shown in Figures 2 and 3, the bending breaking load is larger in Comparative Example 1 than in Example 1 when it is first immersed in 70°C hot water, but even after a few days, the bending breaking load of Example 1 is smaller, and becomes larger than that of Comparative Example 1 after about one day (corresponding to one year). Also, the bending breaking deflection of Comparative Example 1 is significantly lower after about three days (corresponding to three years) compared to when it was first immersed in 70°C hot water, whereas the change in Example 1 is small. Therefore, it can be seen that the glass fiber reinforced concrete of Example 1, which does not contain cement as a binder, is more durable than the glass fiber reinforced concrete of Comparative Example 1, which contains cement as a binder. Therefore, it can be said that the glass fiber reinforced concrete of the present invention is more durable than the conventional glass fiber reinforced concrete when used as a septic tank base plate exposed to the outdoors. [Industrial Applicability]
[0047] The fiber-reinforced concrete base plate for septic tanks of this invention reduces CO2 emissions during product manufacturing and has improved durability compared to conventional fiber-reinforced concrete base plates that use cement as a binder, making it a great advantage when used in septic tanks. [Explanation of symbols]
[0048] 1: Septic tank 2: Septic tank base plate 3. Chestnut layer 4.Drilled holes
Claims
1. The base plate for a septic tank on which the septic tank is placed is made of fiber-reinforced concrete, the fiber-reinforced concrete not containing cement but containing ground granulated blast furnace slag, silica fume, an expansive agent, and hydrated lime as binders, and further containing fine aggregate, glass fiber, and water.
2. A septic tank placed on the septic tank base plate according to claim 1.
Citation Information
Patent Citations
Concrete binding material and concrete using the same
JP2023038451A
Concrete, concrete member, and method for producing concrete
JP2023077790A
Concrete and method of producing the same
JP2023177020A
Septic tank foundation plate and septic tank
JP3197423U